Job Satisfaction as a Mediator Between Educational Technology Training, Affiliation Motivation and Teacher Performance - Mardhatul Fathan; Abd. Rasyid Syamsuri; Sharnuke Asrilsyak (International Journal of Science and Environment (IJSE), 2026)
This study examines the effects of Educational Technology Training and Affiliation Motivation on Teacher Performance through the mediating role of Job Satisfaction at SD Al Ulum Islamic School Pekanbaru. The study employed a quantitative approach using a survey of 40 teachers selected through total sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that Educational Technology Training and Affiliation Motivation significantly improve Job Satisfaction and Teacher Performance. Job Satisfaction also exerts a significant positive effect on Teacher Performance and partially mediates the relationships between Educational Technology Training, Affiliation Motivation, and Teacher Performance. Among the direct relationships examined, Affiliation Motivation demonstrated the strongest effect on Job Satisfaction, highlighting the importance of collaborative work relationships in educational settings. The model explains 83.5% of the variance in Job Satisfaction and 92.4% of the variance in Teacher Performance. These findings contribute to the educational management literature by demonstrating the complementary roles of technological capability development and social motivation in enhancing teacher performance through increased job satisfaction. Practically, schools should strengthen technology-oriented professional development programs while fostering collaborative and supportive work environments to improve teacher effectiveness.